2007
DOI: 10.1111/j.1526-4610.2007.00728.x
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam Prophylaxis in Pediatric Migraine—An Open‐Label Study

Abstract: Levetiracetam had some efficacy in reducing migraine frequency and disability. Further larger studies are warranted, possibly utilizing a placebo-controlled design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 10 publications
0
47
0
3
Order By: Relevance
“…Levetiracetam has been reported to be effective in two open-label studies (Brighina et al, 2006; Pakalnis et al, 2007). The controlled trial reported in chronic daily headache, in which some patients clearly had chronic migraine, was negative (Beran and Spira, 2011).…”
Section: Review Of Literature In Migrainementioning
confidence: 99%
“…Levetiracetam has been reported to be effective in two open-label studies (Brighina et al, 2006; Pakalnis et al, 2007). The controlled trial reported in chronic daily headache, in which some patients clearly had chronic migraine, was negative (Beran and Spira, 2011).…”
Section: Review Of Literature In Migrainementioning
confidence: 99%
“…Two patients (10.5 %) reported no change in headache frequency [28]. In another small open-label study including children ages 6-17 years placed on levetiracetam for migraine prophylaxis (20-40 mg/kg/day), Pakalnis et al [29] found that 18 out of 20 children experienced [50 % reduction in monthly headache frequency (90 % response rate) with a significant decrease in PedMIDAS scores following treatment.…”
Section: Antiepilepticsmentioning
confidence: 95%
“…A practice parameter recently reviewed the available evidence for both acute and preventive therapies in detail as related to pediatric populations [29][30][31][32]. Recent additions to this area have included acute treatments with several triptans; preventive treatment with topiramate [33] and levetiracetam [34]; and the supplement use of coenzyme Q10 [35] and butterbur root extract [36].…”
Section: Treatmentmentioning
confidence: 99%